(untitled) (The Research of Medical Science Review, 2025)
Non-small cell lung cancer (NSCLC) frequently presents with distant metastases, significantly impacting its prognosis and treatment options. The use of 18F-FDG PET-CT proves to be an effective tool for the initial staging of NSCLC. Objective: To evaluate the frequency and patterns of distant metastases in newly diagnosed NSCLC patients at initial presentation using 18F-FDG PET-CT. Methods: Study included 62 biopsy proven NSCLC patients who underwent 18F-FDG PET-CT at initial presentation between March 2024 to August 2024. Demographic data, histopathology, and sites of metastases were recorded and analyzed. Results were documented in designed pro-forma and collected data was evaluated by using SPSS 21.0 for statistical analysis. Age was presented as Mean ±SD. Data was stratified for age, gender and histological subtypes. Frequency and pattern of distant nodal excluding mediastinal (above and below diaphragm), visceral (Liver, Adrenal and other sites) and osseous lesions (axial and appendicular) were tabulated and shown by bar charts. Chi square test was used to determine the dependence between two categorical variables Results: Out of 62 patients, distant metastases were observed in 38 (61.2%) patients. Adenocarcinoma was more common (59.7%) than squamous cell carcinoma (40.3%) and was significantly associated with female gender (P=0.01). The mean age was 58.2 ±10.0 (Range 29-70) years. No significant association was noted between age and frequency of distant metastatic rate (P= 0.6). Regarding pattern of distant metastases, visceral metastases were most common (66%) including adrenal, liver and other sites including brain, muscles and pancreas, followed by osseous (57.8%) and distant nodal metastases (44.7%). Adenocarcinoma demonstrated comparable rates of distant nodal and visceral metastases but was more frequently associated with osseous involvement (64%) while squamous cell carcinoma showed higher prevalence of visceral involvement (85%). Conclusion: 18F-FDG PET-CT shows high efficacy in identifying distant metastases in NSCLC. Adenocarcinoma shows a broader metastatic distribution pattern as compared to squamous cell carcinoma. Employing 18F-FDG PET-CT should be a standard practice for precise M staging at the time of initial diagnosis, aiding in treatment planning while minimizing the need for aggressive therapeutic approaches.